Designing game scenarios for software project management education and assessment. Issue 2 (1st April 2019) - Calderón, Alejandro; Ruiz, Mercedes; O'Connor, Rory V.
Abstract : In recent years, an increasing interest has been observed in the development and use of simulations, serious games (SGs) and gamification strategies to teach software project management (SPM) in a highly practical way. The current SGs for SPM have a quite specific scope, are not able to provide and dynamically change game scenarios during the life of the SG and do not allow teachers to assess students' new skills automatically. These weaknesses led to the development of ProDec, a simulation‐based SG that is able to incorporate SPM real‐life practice. In this study, the authors discuss the use of SGs in SPM education before they describe ProDecAdmin, the game scenario design tool for ProDec. ProDecAdmin provides teachers with an environment for designing the game scenarios for ProDec. Additionally, it helps teachers establish the assessment criteria to automate the students' assessment during the game plays. These functionalities allow ProDec to offer students any game scenario that teachers design and to assess their performance in them. Hence, the tool ProDecAdmin helps the SG ProDec to overcome the lack of flexibility and automatic assessment identified in the current SGs for SPM. This study also outlines the results of the usability evaluation conducted.